The use of finite transmission line elements in numerical analysis - Slater, Geoffrey Ferguson (1973)
The complex nature of solving microwave circuit problems with their many varied boundary conditions, precludes direct analysis utilising the basic laws involved. This thesis describes methods that have been developed to determine the defining parameters of such problems. The methods are based on numerical techniques, using a digital computer to perform the calculations.